the response from the division of intellectual labor to the challenges of diversification and inequality - Pacheco Romero, Luis (2013)
In academic discussion on the road Peruvian society should follow to integral development various problem areas are addressed for analysis and proposals: macroeconomic equilibria, productive diversification (including industrialization), social development (including education, mainly), and environmental conservation. These different paths reveal a specialization of knowledge, which can nevertheless be seen as a perspective not trascending the uni-discipline approach. As many have already remarked, social reality is multi-dimensional; but research endeavours do not always appropriately satisfy that condition when a problem is raised. This paper aims at setting up questions and at going forward in giving proper consideration from a better intellectual division of labour to the main problems of underdevelopment in our society.